Hubungan Kekuasaan pada Tokoh Superhero dan Supervillain dalam Film Iron Man 3 (2013): Sebuah Kajian Tematik - Tobing, Marco Alexandro (UI Scholars Hub, 2014)
This research discusses how superhero and supervillain characters in the fi lmIron Man 3 (2013) shows a power relation as a form of superhuman superiority. The power relation that occur through the confl ict between characters are seen as an establishment of social stratifi cation among superhuman and normal human / society as cultural study. This study is conducted thematically through characterizations analysis method by comparing the defi nition and ideology on the superhero and supervillain in superhero characters, Iron Man and the Iron Patriot, and supervillain character, Mandarin. This study aims to fi nd the root of power relation to the establishment of class structures in the society. By reviewing the defi nition and ideology on these characters, this study is expected to give a broader view of superhuman characters and help the reader to understand the value delivered from superhero character. As a conclusion, the potrayals of the superhero and supervillain characters in the fi lm Iron Man 3 (2013) as the highest power owner have a function to limit and control the values in the society.